Heart failure and arrhythmias: with 17 tables - Brachmann, Johannes; Dietz, Rainer; Kübler, Wolfgang (Springer Berlin Heidelberg, 1990)
This book is a comprehensive update on a highly controver- sial issue in cardiology with the aim to indicate causes for failure of present antiarrhythmic therapy in heart failure and to demonstrate perspectives for the future
Based on an international satellite workshop to the World Congress of Clinical Pharmacology, held in Heidelberg/Mannheim from July 23-29, 1989
Keywords: Konferenzschrift -- 1989 -- Heidelberg; Antiarrhythmikum; Herzinsuffizienz; Pathophysiologie